Expression of TIM‐3 on CD4+ and CD8+ T cells in the peripheral blood and synovial fluid of rheumatoid arthritis. Issue 10 (23rd February 2014) - Li, Shufeng; Peng, Dayong; He, Yeteng; Zhang, Hu; Sun, Huaqiang; Shan, Shiying; Song, Yuanlin; Zhang, Shuzhen; Xiao, Hong; Song, Haihan; Zhang, Ming
<x xml:space="preserve">Abstract</x> Rheumatoid arthritis (RA) is characterized by a chronic inflammatory process that targets the synovial lining of diarthrodial joints. TIM‐3 plays a key role in the negative regulation of the immune response. In this study, we investigated the expression of TIM‐3 on CD4+ and CD8+ T cells from systemic (peripheral blood) and local (synovial fluid) perspectives of RA. Level of TIM‐3+ cells from peripheral blood and synovial fluid of patients as well as peripheral blood of healthy controls was measured by flow cytometry. Results showed that TIM‐3 expression was significantly increased in both CD4+ and CD8+ T cells in the peripheral blood of RA (p < 0.001 and p < 0.001, respectively). Furthermore, patients revealed even higher expression of TIM‐3 in CD4+ and CD8+ T cells in synovial fluid than in peripheral blood. When comparing TIM‐3 level with the severity of RA, we identified that the percentage of TIM‐3 on both peripheral CD4+ and peripheral CD8+ T cells was negatively correlated with disease activity score 28 (DAS28) of the patients. Similarly, TIM‐3 on synovial fluid CD4+ and CD8+ T cells also revealed inverse correlation with DAS28 of the cases. Our data demonstrate a negative correlation between TIM‐3 and the disease progression of RA.